2016
DOI: 10.1002/zoo.21264
|View full text |Cite
|
Sign up to set email alerts
|

Group compositional changes impact the social and feeding behaviors of captive hamadryas baboons (Papio hamadryas hamadryas)

Abstract: The formation and modification of social groups in captivity are delicate management tasks. The ability for personnel to anticipate changes in group dynamics following compositional changes can increase the likelihood of successful management with minimized injury or social instability. Hamadryas baboons (Papio hamadryas hamadryas) have a distinctive multi-level social system comprising of one-male units (OMUs) that can make it difficult to apply knowledge from other primates' multi-female/multi-male social st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Much of the SNA research involving captive animals has been conducted concerning the effect of environmental changes and the removal of individuals on the social behaviors of primates; however, little research has examined the impacts of the addition of individuals to an established group (Beisner et al, 2011; Beisner et al, 2015; Brent et al, 2011; Flack et al, 2005; Hansen et al, 2009; Less et al, 2010). Ryan and Hauber (2016) examined the compositional changes of a group of captive hamadryas baboons following an introduction of two females. Researchers found that social interactions increased and that behavior was primarily affiliative rather than agonistic.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the SNA research involving captive animals has been conducted concerning the effect of environmental changes and the removal of individuals on the social behaviors of primates; however, little research has examined the impacts of the addition of individuals to an established group (Beisner et al, 2011; Beisner et al, 2015; Brent et al, 2011; Flack et al, 2005; Hansen et al, 2009; Less et al, 2010). Ryan and Hauber (2016) examined the compositional changes of a group of captive hamadryas baboons following an introduction of two females. Researchers found that social interactions increased and that behavior was primarily affiliative rather than agonistic.…”
Section: Introductionmentioning
confidence: 99%
“…Different feeding situations in captivity can affect behavior and social groups in captive baboons. Particularly, aggression between hamadryas baboons is reduced when food is dispersed, rather than clumped (Gil‐Burmann et al, 1998; Ryan & Hauber, 2016). The captive feeding situation can also affect cohesiveness, with OMUs being less cohesive when food is dispersed (Gil‐Burmann et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Since feeding, space limitations, and relatability are largely different in the wild than in captivity for hamadryas baboons, these studies lead us to believe captivity itself could affect any of the OMU formation pathways. In addition, Ryan and Hauber (2016) did observe social behavior after an introduction of two females to a captive hamadryas baboon group. However, the creation of OMUs after the initial introduction was not organic, as zoo staff removed females from one group to create an entirely separate OMU with the new females and another male.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a multilevel society of hamadryas baboons (Papio hamadryas), juvenile males leave their natal OMU at around two years of age. These males remain on the periphery of their natal breeding clan, which is composed of several patrilineally related OMUs (Sigg et al, 1982;Bergman et al, 2008;Ryan & Hauber, 2016). Young males that have left their natal OMU employ a "follow-and-wait-strategy" (Mori et al, 2007), occasionally approaching infant and juvenile females to become familiar with these potential future sexual partners (Chalmers, 1986; see also for olive baboons: Danish & Palombit, 2014).…”
Section: Introductionmentioning
confidence: 99%